2018
DOI: 10.1038/s41598-018-35380-w
|View full text |Cite
|
Sign up to set email alerts
|

The association between spirituality and religiousness and mental health

Abstract: The present study aims to investigate how different levels of spirituality and religiousness (high spirituality and high religiousness –S/R, high spirituality and low religiousness –S/r, low spirituality and high religiousness s/R and low spirituality and low religiousness – s/r) are associated with quality of life, depressive symptoms, anxiety, optimism and happiness among adults. A cross-sectional study was carried out among 1,046 Brazilian adults. Concerning the different levels of spirituality and religiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
74
1
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 64 publications
(67 reference statements)
5
74
1
19
Order By: Relevance
“…Note that there is a clear overlap between psychological QoL and mental disorders and four of the studies included in this review found positive associations between S/R and depression and stress [28,38,40,41]. In this line, other studies addressing mixed samples of adults and elderly individuals, healthy and unhealthy people, also report a relationship between higher levels of S/R with improved psychological QoL and decreased stress and depression, according to the in uence of facets such as peace, meaning, optimism and happiness [5,48].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Note that there is a clear overlap between psychological QoL and mental disorders and four of the studies included in this review found positive associations between S/R and depression and stress [28,38,40,41]. In this line, other studies addressing mixed samples of adults and elderly individuals, healthy and unhealthy people, also report a relationship between higher levels of S/R with improved psychological QoL and decreased stress and depression, according to the in uence of facets such as peace, meaning, optimism and happiness [5,48].…”
Section: Discussionmentioning
confidence: 62%
“…Among the QoL components most frequently associated with S/R, the psychological component was the most important. The most signi cant evidence available in the S/R eld is related to mental health [5,19,25,48]. Nine of the studies in this review report positive associations between S/R and some mental health parameters.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The World Health Organization Quality of Life Assessment group defined QoL as the individual's perceptions of their position in life in the context of the culture and value system in which they live, and regarding their goals, expectations, patterns, and concerns 3 . Several factors are said to influence QoL [3][4][5] , such as sociodemographic status (gender, age, education level, and marital status), physical health (such as energy, fatigue, pain, sleep quality), and a person's psychological status (physical appearance, positive/negative feelings, selfesteem). People also occupy social and physical spaces.…”
mentioning
confidence: 99%
“…Thus, the relationships in terms of social support and sexual activity, and aspects of the surrounding physical and home environment (financial situation, freedom, safe environment, recreation, transportation, climate, pollution), can affect one's QoL. Religious/spiritual status also refers to social and physical spaces, as one believes in and seeks support from members of one's religious community, attends in places of worship, receives support, provide religious attendance, meaning in life, peace, optimism, faith [3][4][5] .…”
mentioning
confidence: 99%